Effect of subsurface water level on gully headcut retreat in tropical highlands of Ethiopia. Issue 6 (4th March 2021) - Yibeltal, Mesenbet; Tsunekawa, Atsushi; Haregeweyn, Nigussie; Adgo, Enyew; Meshesha, Derege Tsegaye; Masunaga, Tsugiyuki; Tsubo, Mitsuru; Billi, Paolo; Ebabu, Kindiye; Liyew Berihun, Mulatu
Abstract: Gully erosion is a major cause of soil loss and severe land degradation in sub‐humid Ethiopia. The objective of this study was to investigate the role and the effect of subsurface water level change on gully headcut retreat, gully formation and expansion in high rainfall tropical regions in the Ethiopian highlands. During the rainy seasons of 2017–2019, the expansion rate of 16 fixed gullies was measured and subsurface water levels were measured by piezometers installed near gully heads. During the study period, headcut retreats ranged from 0.70 to 2.35 m, with a mean value of 1.49 ± 0.56 m year −1, and average depth of the surface water level varied between 1.12 and 2.82 m, with a mean value of 2.62 m. Gully cross‐section areas ranged from 2.90 to 20.90 m 2, with an average of 9.31 ± 4.80 m 2 . Volumetric retreat of gully headcuts ranged from 4.49 to 40.55 m 3 and averaged 13.34 ± 9.10 m 3 . Soil loss from individual gullies ranged from 5.79 to 52.31 t year −1 and averaged 17.21 ± 11.74 t year −1 . The headcut retreat rate and sediment yield were closely related over the three study seasons. Elevated subsurface water levels facilitated the slumping of gully banks and heads, causing high sediment yield. When the soil was saturated, bank collapse and headcut retreat were favoured by the combination of elevated subsurface water and high rainfall. This study indicates that area exclosures are effective in controlling subsurface water level, thus reducing gully headcut retreat and associated soil loss. Abstract : Subsurface water flow increases gully headcut retreat in the sub‐humid tropical highlands of Ethiopia. Elevated subsurface water levels facilitated the slumping of gully banks and heads, causing high sediment yield. The area exclosure decreases both gully headcut and it is very important for developing gully management approaches for high rainfall tropical regions.